Cooperation - an effective form of labor organization in the village - I. S. Maltseva; Y. I. Tarasov (Новые технологии, 2017)
The article examines the role and importance of agricultural cooperatives, their influence on the formation and development of small-scale forms of economy management. Factors restraining the development of agricultural cooperatives are analyzed, and organizational and economic measures for their elimination are proposed.